2021
DOI: 10.20414/jed.v3i01.3367
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy and Islamic Bank Stability in Indonesia

Abstract: The purpose of this paper is to examine the role of monetary policy to Islamic Bank Stability in Indonesia from January 2007 to December 2020. The policy is presented by Bank Indonesia 7DRR while Islamic Bank Stability uses Islamic Bank Z-score. This paper also employs several variables as control variable in order to manage effectiveness of the model. This paper uses Autoregressive Distributed Lag method (ARDL) in order to investigate the long run and short run effect between selected variables. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This is an open-access article under the CC-BY license. monetary policy in Indonesia, although they were focused mostly in banking sectors [3]. Researches had found that Islamic banking is very different from the conventional bank system [4].…”
Section: Islamic Monetary System Sharia Banks Bi 7 Days Reverse Repo ...mentioning
confidence: 99%
“…This is an open-access article under the CC-BY license. monetary policy in Indonesia, although they were focused mostly in banking sectors [3]. Researches had found that Islamic banking is very different from the conventional bank system [4].…”
Section: Islamic Monetary System Sharia Banks Bi 7 Days Reverse Repo ...mentioning
confidence: 99%